The Value Relevance of Accounting Information of Listed Companies in ASEAN Countries - Kobkanjanapued, Yodsawinkan; Tripattanasit, Pimonwan (Arts of Management Journal, 2023)
This article aimed to (1) study the value relevance of book value per share, earnings per share, and operating cash flow per share of listed companies in Singapore, Malaysia, Thailand, Indonesia, and the Philippines; and (2) to study the differences and compare the value relevance of book value per share, earnings per share, and operating cash flow per share between listed companies in Singapore, Malaysia, Indonesia, and Philippines with Thailand during 2017 - 2019. The sample was listed companies in Thailand, Singapore, Malaysia, Indonesia, and The Philippines. They were selected by specified characteristics. The data was analyzed using descriptive statistics, correlation analysis, and multiple regression analysis techniques. The results show that book value per share, earnings per share, and operating cash flow per share of listed companies in ASEAN countries (all five countries) are related to explaining stock prices in a positive direction. In addition, the research found that listed companies in ASEAN countries have no differences in book value, earnings per share, and operating cash flow in explaining stock prices in each country, except for listed companies in Singapore, which are different from those in Thailand in explaining the stock price of earning per share.